Navigation Guidance and Interactive Mobile Application Features for the Visually Impaired - Naik, Darsh Ashik; Mishra, Bhavya; Narayanaxsamy, Praveen (International Journal of Psychosocial Rehabilitation, 2020)
Visually impaired people have always found difficulties in detecting the obstacles in front of them particularly during walking on the street, proving it to be dangerous. This project has been proposed as a solution for aiding these visually impaired or partially sighted people by developing an intelligent system. Information regarding the direction and obstruction detection would be provided to the user, this would be done by using ultrasonic sensors, a vibrator motor, and a buzzer. The intensity of the vibration would increase or decrease with respect to whether the detected object is closer or farther. Moreover, the system would provide a Mobile Application interface which would be designed to be connected by the hardware module and would help perform various tasks without the user ever touching the mobile phone. The mobile application would accept voice commands from the user to perform various tasks. The tasks would include telling the user’s current location and aiding the user to go to the desired destination. This whole system would be activated by voice commands. The proposed system would be designed to be compact and would weigh less. The module would be incorporated with the cane, making the visually challenged persons walk with more confidence and independence. The system will provide safety.